Stable expression in yeast of the mature form of human telomerase RNA depends on its association with the box H/ACA small nucleolar RNP proteins Cbf5p, Nhp2p and Nop10p - Dez, Christophe (Oxford University Press, 2001)
Telomerase is a ribonucleoprotein (RNP) particle required for the replication of telomeres. The RNA component, termed hTR, of human telomerase contains a domain structurally and functionally related to box H/ACA small nucleolar RNAs (snoRNAs). Furthermore, hTR is known to be associated with two core components of H/ACA snoRNPs, hGar1p and Dyskerin (the human counterpart of yeast Cbf5p). To assess the functional importance of the association of hTR with H/ACA snoRNP core proteins, we have attempted to express hTR in a genetically tractable system, Saccharomyces cerevisiae. Both mature non-polyadenylated and polyadenylated forms of hTR accumulate in yeast. The former is associated with all yeast H/ACA snoRNP core proteins, unlike TLC1 RNA, the endogenous RNA component of yeast telomerase. We show that the presence of the H/ACA snoRNP proteins Cbf5p, Nhp2p and Nop10p, but not Gar1p, is required for the accumulation of mature non-polyadenylated hTR in yeast, while accumulation of TLC1 RNA is not affected by the absence of any of these proteins. Our results demonstrate that yeast telomerase is unrelated to H/ACA snoRNPs. In addition, they show that the accumulation in yeast of the mature RNA component of human telomerase depends on its association with three of the four core H/ACA snoRNP proteins. It is likely that this is the case in human cells as well.